2006
DOI: 10.1097/01.rli.0000236910.75905.cc
|View full text |Cite
|
Sign up to set email alerts
|

Navigation-Based Needle Puncture of a Cadaver Using a Hybrid Tracking Navigational System

Abstract: Needle puncture in a soft tissue environment using the navigational system Medarpa can be reliably performed and matches the accuracy achieved by a computed tomography-guided puncture technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 41 publications
0
33
0
1
Order By: Relevance
“…2,4 To address this issue, several navigation systems have been introduced which can guide the physician towards a preselected target (e.g. [5][6][7][8][9][10][11][12][13] ). The overall insertion error of these systems typically comprises (cf.…”
Section: Purposementioning
confidence: 99%
“…2,4 To address this issue, several navigation systems have been introduced which can guide the physician towards a preselected target (e.g. [5][6][7][8][9][10][11][12][13] ). The overall insertion error of these systems typically comprises (cf.…”
Section: Purposementioning
confidence: 99%
“…Zhang et al [2] reported a success rate of 87.5% (n = 16) in a silicon liver mounted onto a motion simulator and a mean targeting error of 8.3 ± 3.7 mm (n = 32) in swine. Other groups obtained mean errors of 8.4 ± 1.8 mm (n = 42) in human cadavers [3] and 6.4 ± 1.8 (n = 22) in ventilated swine [1].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [2] implanted tumor models containing radio-opaque CT contrast medium into a silicon liver model mounted on a motion simulator and also conducted experiments in swine with agar injections as nodular targets. Kahn et al [3] evaluated their navigation system in human cadavers, with three different targets: a predefined position within the ascending aorta, a calcified plaque in an artery, and the tip of a port catheter. Fichtinger et al [1] conducted experiments in ventilated swine cadavers and used stainless-steel staples as targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the area of needle guidance applications, many navigation systems have been developed to solve specific clinical problems, such as liver puncture [7,8] and vertebroplasty procedures [9], as well as for general biopsy procedures [10,11]. While some groups [9][10][11] rely on well established rigid approaches for registering the patient to the image and are therefore limited to targeting static anatomical regions, other groups have investigated nonrigid methods to gate breathing [7] or to model deformation [8] in order to target organs that can deform considerably during the procedure. A recent review by Cleary and Peters [12] shows that even though non-rigid methods are making progress for interventions in the thorax and abdomen, most current work is still based on the rigid approach.…”
Section: Introductionmentioning
confidence: 99%